(3JaSjQ GHf ahQcs - (3CHh HcQ eMeO Hf GdMSf GdfjSGHhQj GdTGaYj,J (B406 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ Ghd ShQI GdeDefjf s
(3BNQgG (B:s
(3jfJgi HBNQ GdbQBf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B439s
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(50) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs